NILAI TAMBAH PRODUKSI MOULDING DARI BEBERAPA PERUSAHAAN DI JAWA TIMUR DAN SUMATERA SELATAN - Sylviani Sylviani; Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1987)
Study about added value have done in relation with the diversification  of  wood working.  Product  of moulding  Is one of the export product commondity   which could contribute  to increase foreign  exchange earning.  The obyective  of the study  is to conduct  a study  on several sawmills in South  Sumatera  and East Java.Average sawn timber  waste and sawntimber  that could be produce  are 14. 600,50 cu. meter per industry each year.  Those material which can be processed  into moulding  is 4.919, 75 cu. meter  a year. Rendement of moulding  that originated from  sawntimber   waste is less than 25 percent, and the one from  sawn timber  is 50 percent.The factory  added value which yields profit  is 226.863.832 rupiahs a year or 28.559 rupiahs per cu.m  moulding.  Income  share distributed among  of  equipment  factors are 34.273,50  rupiahs  per  cu.m   (35,8  percent),   labour  26.000   rupiahs  per  cu.m  (27,2  percent), materials 6.892,50  rupiahs per cu.m  (7,2 percent)  and manager 28.559,02  rupiahs per cu.m  (29,8 percent).Average  employment   opportunity   to produce for  each industri  is 73.853 mandays  or 516.973 manhours  a year.  Because  the sawntimber waste and sawn timber  was profitable  to produce  moulding,  it is advisable that activities in the sawmills should  be directed to produce  moulding.